Psychometric Testing of HeLD-14 in a Colombian Geriatric Population - Ana Cristina Mafla; Mauricio Herrera-López; Carmen Gallardo-Pino; Falk Schwendicke (Hindawi Limited, 2024)
Introduction. The objective of this study was to test the validity and reliability of the Colombian version of the Health Literacy in Dentistry (HeLD-14) in older adults. Materials and Methods. A translation and validation study of HeLD-14 was conducted on 384 non-institutionalized older adults attending the Dental Clinic at Universidad Cooperativa from Pasto, Colombia. A cross-cultural adaptation of a multidimensional HeLD-14 was completed, and the psychometric properties of this scale were evaluated through a cross-validation method using an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). Internal consistency was measured with Cronbach's alpha (α) and Omega's McDonald (ɷ). The statistical significance was set at P<0.05. Results. The EFA demonstrated that a single-factor structure with 11 items explained a cumulative 59.86% of the overall variance. The CFA confirmed that goodness of fit indices of this questionnaire had optimal adequateness (χ2S-B = 109.047; χ2S-B/(44) = 2.478, P=0.001; non-normed fit index = 0.901; comparative fit index = 0.908; root mean square error of approximation = 0.079 (90% CI (0.075, 0.083)); standardized root mean residual = 0.080). The coefficients indicated a high internal consistency for the total scale (α = 0.94; ɷ = 0.96). Conclusion. The developed adaptation of HeLD-14 for the Colombian population, HeLD-Col, is a unidimensional, reliable, and valid instrument to assess oral health literacy in older adults in Colombia.